Conservatism on Islamic Legal Maxims: Judicial Interpretation of Polygamous Marriage at the Religious Courts of Mojokerto, Indonesia - Mukhammad Nur Hadi; Latifatul Islamiyah; Cecep Soleh Kurniawan (Journal of Islamic Law)
This article explores religious judges’ interpretations of Islamic legal maxims through a content analysis of 30 verdicts that granted permission for husbands’ polygamous marriages issued by the Religious Court of Mojokerto in Indonesia from 2020 to 2022. Despite governmental efforts to restrict polygamous marriage practices due to potential negative consequences, religious judges often grant permission to husbands, considering a balance between maṣlaḥah (public good) and mafsadah (harm). Employing a normative-philosophical approach, this article identifies two recurring Islamic legal maxims consistently applied by judges: “dar’u al-mafāsid muqaddamun ‘alā jalb al-maṣāliḥ” and “idhā taʼārada mafṣadaṭānī rūʼiya aʼẓamuhumā ḍararan bi al-’irtikābi akhaffihimā.” However, their legal interpretations regarding maṣlaḥah and mafsadah reinforce the husband’s interest in the case of polygamous marriage. Thus, the authors argue that the interpretations of these legal maxims in practice reflect a conservative perspective that strengthens patriarchal hierarchies. These findings highlight that Islamic legal maxims as legal principles within Islam have not yet effectively functioned as an instrument of protection for vulnerable groups, especially women and children.